Studi analisis manfaat limbah fly ash pada industri bahan baku semen - Permatasari, Ratih (Energy Justice, 2024)
Background: The demand for electrical energy and dependence on coal energy sources, while the coal combustion process does not burn out, resulting in waste in the form of fly ash. The utilization of fly ash waste in the cement industry can potentially cause environmental impacts in the form of air pollution. Therefore, the concept of sustainability of fly ash waste utilization as an alternative raw material in the cement industry is needed. The objectives of this study are to analyze the potential environmental impacts on the utilization of fly ash waste into cement, analyze the financial benefits for the cement industry, and determine alternative sustainability of fly ash waste utilization based on the concept of clean production. Methods: The research method used is quantitative method with AHP method. Findings: The results showed that particulate concentrations in fly ash waste utilization activities did not exceed quality standards but had the potential to cause environmental impacts with a 24-hour period distribution of 219 µg/m3, while the highest annual period was 67.2 µg/m3. Utilization of fly ash waste can reduce the use of gypsum and trass raw materials by up to 3.2%. The financial benefits received by the cement industry are material cost efficiency of Rp6,052,872,369.02 in 2018 and Rp32,730,142,087.09 in 2022. Conclusion: The concept of clean production as an alternative to the sustainability of fly ash waste utilization in the cement industry of PT ABC is to implement the recycle of particulates captured by DC and EP.